PRAKTIK PENGALAMAN LAPANGAN (PPL) BERBASIS LESSON STUDY PADA MAHASISWA PAI UIN ABDURRAHMAN WAHID PEKALONGAN - Vera Atika Sari; M. Adin Setyawan (ADDABANA: Jurnal Pendidikan Agama Islam, 2025)
Abstract: Field Experience Practice (PPL) is a compulsory course for the PAI Study Program with a weight of four credits which is carried out for fifty days at school. So far, Lesson Study has been carried out in schools by teachers in order to foster and develop the teaching profession. One of the objectives of implementing PPL based on Lesson Study is to equip students as prospective teachers to practice implementing it in the classroom. The research method uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews and Forum Group Discussion. The research sample consisted of nine PAI Study Program students who were carrying out PPL. Judging from the implementation of the research, this research is classified as action research based on Lesson Study. The qualitative research data analysis technique refers to the results of field notes including teaching modules and notes on observation and reflection results. The results of the study showed that the implementation of Lesson Study was proven to support the improvement of prospective teacher competencies in compiling teaching materials and managing teaching and learning activities effectively.Keywords: Lesson Study, PPL, PAI.  Abstrak: Bagi Program Studi PAI, Praktik Pengalaman Lapangan (PPL) merupakan mata kuliah wajib bernilai empat SKS yang diselesaikan selama lima puluh hari di sekolah menengah pertama dan sekolah menengah atas hingga saat ini, guru telah menerapkan Lesson Study di sekolah untuk mendukung dan memajukan profesi guru. Tujuan diterapkannya PPL berbasis Lesson Study salah satunya membekali mahasiswa sebagai calon guru untuk berlatih menerapkannya di kelas. Penelitian ini menggunakan metodologi deskriptif kualitatif, dengan pengumpulan data melalui dan Forum Group Discusssion (FGD), wawancara, dan observasi. Sampel penelitian terdiri atas sembilan orang mahasiswa Prodi PAI UIN Abdurrahman Wahid Pekalongan yang sedang melaksanakan PPL. Ditinjau dari pelaksanaan penelitian, maka penelitian ini digolongkan dalam penelitian tindakan berbasis Lesson Study. Teknik analisis data penelitian kualitatif mengacu pada hasil catatan lapangan meliputi modul ajar dan catatan hasil observasi serta refleksi. Hasil penelitian menunjukkan pelaksanaan Lesson Study terbukti mendukung peningkatan kompetensi calon guru dalam menyusun perangkat ajar dan mengelola KBM secara efektif.Kata Kunci: Lesson Study, PPL, PAI.